Penerapan Project Based Learning dalam Peningkatkan Kemampuan Matematik Mahasiswa pada Materi Kalkulus Integral - Dahlan Wahyudi; Winda Syam Tonra; Wilda Syam Tonra; Nurma Angkotasan; Joko Suratno (Universitas Ma'arif Lampung, 2026)
Students often experience difficulties in learning integral calculus; therefore, instructional innovation is needed to improve their mathematical abilities. This study aims to examine the effect of implementing Project-Based Learning (PjBL) on students’ mathematical abilities in the topic of integral calculus. The research employed a pre-experimental method with a quantitative approach using a one-group pretest–post-test design. The data were obtained from tests administered before and after the treatment. To determine the difference in students’ abilities between the pretest and post-test results, the data were analysed using IBM SPSS Statistics version 21 through the paired samples t-test procedure. The test results showed a Sig. 2-tailed value of 0.000, which was below the significance level of 0.05. These results indicate a significant difference in students’ mathematical abilities before and after learning through the PjBL model. This finding shows that project-based learning is effective in developing students’ mathematical abilities in integral calculus. Therefore, PjBL can be used as a relevant alternative learning model to support the improvement of students’ mathematical abilities.